History, Economy and Administration in Late Iron Age Judah in Light of the Excavations at Mordot Arnona, Jerusalem - Sapir, Neria; Ben-Ari, Nathan; Froid, Liʾorah 1955-; Lipshits, ʿOded 1963- (2022)
The site of Mordot Arnona is located ca. 750 m northeast of Ramat Rahel and on the eastern outskirts of the Arnona neighbourhood of Jerusalem. Few sites around Jerusalem present a stratigraphy and settlement sequence that includes nine building and construction phases, dating from the Late Iron IIA (9th century BCE) to the Late Roman period (4th century CE). During much of this time, and especially between the late 7th century BCE and the 4th century CE, the site was a small agricultural settlement. In the late 8th and the first half of the 7th century BCE, however, Mordot Arnona held great significance in the physical and political landscape of the area south of Jerusalem, serving as an administrative centre, as evidenced by its monumental structures and the dozens of stamped jar handles. In this paper we present a preliminary description of the site and the main finds from the monumental stage in its history, along with our initial conjectures regarding the role of this site, together with Ramat Rahel, in the history of the Kingdom of Judah during the last 150 years of its existence.
Keywords: Ramat Rahel; Stamp impressions; lmlk; Assyrian Empire; Biblical period; Jerusalem; Iron Age; Kingdom of Judah